PENGARUH STRATEGI MANAJERTAL TERHADAP HUBUNGAN ANTARA PENGGUNAAN ANGGARAN DENGAN PENINGKATAN KINERJA MANAJERIAL - DERMAWAN SJAHRIAL (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2006)
This study investigates the influence of managerial strategic on the relationship between budgeting design usage and managerial performance. The objectives of this study are: (1) to investigate the relationship between budgeting design usage and managerial performance and (2) to investigate the effect of managerial strategic in the relationship between budgeting design usage and managerial performance. The expectations in the model were explored with data gathered from 26 public banks in Bursa Efek Jakarta. The study uses a research methodology survey method supplemented by questionnaire, the survey questionnaire is adapted from previous studies. The respondents of the survey questionnaire were Chief Executive Officers and Middle Managers responsible for unit budgets in the sample of companies.The result of the study are : (1) there is a significant relationship between budgeting design ugase and managerial performance. (2) there is a significant relationship between budgeting design usage and managerial performance is moderated by managerial strategic.